Integrating molecular rigidity and chirality into thermally activated delayed fluorescence emitters for highly efficient sky-blue and orange circularly polarized electroluminescence. Issue 2 (19th November 2020) - Ni, Fan; Huang, Chih-Wei; Tang, Yukun; Chen, Zhanxiang; Wu, Yaxun; Xia, Shengpeng; Cao, Xiaosong; Hsu, Jung-Hsien; Lee, Wei-Kai; Zheng, Kailu; Huang, Zhongyan; Wu, Chung-Chih; et al.
Abstract : Two pairs of D*–A type blue and orange CP-TADF emitters based on a rigid point chiral donor reveal high molecular rigidity, excellent PLQYs, and intense luminescence dissymmetry factors, which jointly enable highly efficient CP-OLEDs. Abstract : By integrating high molecular rigidity and stable chirality, two pairs of D*–A type circularly polarized thermally activated delayed fluorescence (CP-TADF) emitters with an almost absolute quasi-equatorial conformer geometry and excellent photoluminescence quantum efficiencies (PLQYs) are developed, achieving state-of-the-art electroluminescence performance among blue and orange circularly polarized organic light-emitting diodes (CP-OLEDs).